A Natural Variation in PLEIOTROPIC DEVELOPMENTAL DEFECTS Uncovers a Crucial Role for Chloroplast tRNA Modification in Translation and Plant Development. Issue 7 (23rd April 2020) - Liu, Hui; Ren, Ding; Jiang, Ling; Li, Xiaojing; Yao, Yuan; Mi, Limin; Chen, Wanli; Mo, Aowei; Jiang, Ning; Yang, Jinshui; Chen, Peng; Ma, Hong; et al.
Abstract : Chloroplast tRNA modification influences protein translation, leading to pleiotropic developmental defects in rice, as revealed by analysis of a natural allele of tRNA-modifying GTPase gene PDD . Abstract: The modification of tRNA is important for accurate, efficient protein translation. A number of tRNA-modifying enzymes were found to influence various developmental processes in distinct organisms. However, few genetic or molecular studies have focused on genes encoding tRNA-modifying enzymes in green plant organelles. Here, we discovered that PDD OL, a natural variation allele of PLEIOTROPIC DEVELOPMENTAL DEFECTS ( PDD ), leads to pleiotropic developmental defects in a near-isogenic line (NIL) generated by introgressing the wild rice Oryza longistaminata into the rice ( Oryza sativa ) cv 187R. Map-based cloning revealed that PDD encodes an evolutionarily conserved tRNA-modifying GTPase belonging to the tRNA modification E family. The function of PDD was further confirmed by genetic complementation experiments and mutant analysis. PDD mRNA is primarily expressed in leaves, and PDD is localized to chloroplasts. Biochemical analyses indicated that PDD 187R forms homodimers and has strong GTPase activity, whereas PDD OL fails to form homodimers and has weak GTPase activity. Liquid chromatography–coupled tandem quadrupole mass spectrometry revealed that PDD is associated with the 5-methylaminomethyl-2-thiouridine modification of chloroplast tRNA. Furthermore, compared to 187R, NIL- PDD OL has severely reduced levels of proteins involved in photosynthesis and ribosome biogenesis but increased levels of plastid-encoded RNA polymerase subunits. Finally, we demonstrate that the defect due to PDD OL alters chloroplast gene expression, thereby affecting communication between the chloroplast and the nucleus.